Comportamento reológico de emulsões do tipo água em óleo de petróleos pesados : estudo experimental e avaliação de correlações empíricas - Ferraz, Ludian Anacleto (2015)
In general, when the oil fields get older the amount of produced water increases. This increase tends to cause the undesirable situations, such as the production of stable emulsions with high viscosities that to be pumped require larger capacity equipment, besides, they demand more energy for processing. From the point of view of project design, another disadvantage is the uncertainty found in the thermo-hydraulic calculations of pipes due to the use of inadequate information in regard to the rheological properties of emulsions. Inadequate predictions can result in incorrect sizing of equipment with potential economic impacts. In this work, in order to evaluate some of the main empirical correlations, aimed at predicting viscosities of the water-in-oil emulsions (W/O) and present in two of the most prominent multiphase flow simulators (OLGA® , PIPESIM® ), were collected four (4) oil samples from oil wells from petroleum fields of the North Capixaba, with API degree between 13 and 23, and through Design of Experiments (DOE), the influence of the temperature, volume fraction of dispersed phase and shear rate on the relative viscosities of the emulsions were evaluted. The effect of volume fraction of the dispersed phase proved to be highly significant, while the effect of temperature and shear rate proved to be insignificant. By way of further testing was possible to compare empirical correlations proposed in the literature and conclude that the correlations Brinkman (1952), Vand (1948) and Pal and Rhodes (1989) showed satisfactory results for predicting the behavior of emulsions produced by heavy oil.